2021
DOI: 10.3390/microorganisms9050902
|View full text |Cite
|
Sign up to set email alerts
|

Capripoxvirus Infections in Ruminants: A Review

Abstract: Lumpy skin disease, sheeppox, and goatpox are notifiable diseases of cattle, sheep, and goats, respectively, caused by viruses of the Capripoxvirus genus. They are responsible for both direct and indirect financial losses. These losses arise through animal mortality, morbidity cost of vaccinations, and constraints to animals and animal products’ trade. Control and eradication of capripoxviruses depend on early detection of outbreaks, vector control, strict animal movement, and vaccination which remains the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 126 publications
(165 reference statements)
0
38
0
Order By: Relevance
“…A large proportion (approximately 50%) of vaccinated animals do not develop antibody responses, yet they are protected against LSD [16]. The interplay between humoral and T cell responses is not fully understood for LSDV, but both arms of the immune response are recognized as being important [27,73,74]. A balanced CD4 + and CD8 + T cell response specific to LSDV was elicited against a dual vaccine against LSDV and Rift Valley fever virus [75].…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion (approximately 50%) of vaccinated animals do not develop antibody responses, yet they are protected against LSD [16]. The interplay between humoral and T cell responses is not fully understood for LSDV, but both arms of the immune response are recognized as being important [27,73,74]. A balanced CD4 + and CD8 + T cell response specific to LSDV was elicited against a dual vaccine against LSDV and Rift Valley fever virus [75].…”
Section: Discussionmentioning
confidence: 99%
“…However, LSDV has significantly increased in Asia, including Russia, China, India, Thailand, Malaysia, Sri-Lanka, Bangladesh and Vietnam (Fig. 1 B) (FAO 2017a ; Hamdi et al 2021 ), and frequent outbreaks of LSD in Greece were reported in the past, with occasional outbreaks of LSD in Bulgaria due to outbreaks that occurred in Turkey (OIE 2008 ).
Fig.
…”
Section: Literature Reviewmentioning
confidence: 99%
“…B Lumpy skin disease geographic distribution. Source: (Hamdi et al 2021 ). The red color indicates the presence of CaPV …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumpy skin disease (LSD) and bovine ephemeral fever (BEF) are two cattle diseases of economic importance with low mortality but high morbidity rates [1][2][3]. LSD is classified as a notifiable disease by the World Organization for Animal Health (OIE); it is characterized by fever, clinical lesions which affect animal hides, reduced milk yields and abortion in pregnant ewes [2,4]. It was initially confined to Africa, but spread to Egypt in 1988, Israel in 1989, followed by the Middle East in the 1990s [5].…”
Section: Introductionmentioning
confidence: 99%